Basic Motor Ability: Aquatic Learning for Early Childhood (Department of Physical Education, Sport, Health and Recreation, 2019)
This study aimed to determine the impacts of aquatic learning on the basic motoric abilities of early childhood. Experimental research of one group pretest-posttest design was applied in this study. This study involved eight kindergarten students: aged 5-6 years. This study was conducted twice a week for 4 weeks; 60 minutes per meeting. The instruments were structured observation, field notes, and documentation of the child’s basic motor consisting of 9 aspects, namely water orientation, water entry, breath control, body position, buoyancy, arm propulsion, arm recovery, leg action, and combined movement. The data analysis technique used was paired sample t-test. The results showed an increase in basic motor skills of early childhood with P <0.05. From 9 aspects of assessment, the aspect of arm propulsion got the highest increase of 31.25% while the water orientation aspect got the lowest increase of 16.7%. The highest achievement of all aspects is achieved in the aspect of water orientation, which indicates that all children can do it well. Therefore, there was a positive influence of the provision of aquatic learning on improving basic motor skills for early childhood